2012
DOI: 10.1292/jvms.11-0415
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte Blastogenic Responses to Food Antigens in Cats Showing Clinical Symptoms of Food Hypersensitivity

Abstract: ABSTRACT. Three cats were diagnosed as having food hypersensitivity by food elimination and oral food provocation tests. Twelve allergenic food ingredients were identified by oral food provocation test in the 3 cats. Of the 12 food ingredients, 9 offending food antigens were shown to be positive in a lymphocyte stimulation test; however, none of them were positive in antigen-specific IgE testing, and only four food antigens were positive in intradermal testing. The stimulation indices in the lymphocyte stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Numerous dietary items have been reported to cause CFA in cats ( Table 1). The most commonly identified items were cow's milk (15 cats) 4,12,17,29,31) , fish (10 cats) 12,17,23,31) , beef (10 cats) 12,17,29) , chicken (4 cats), 17,22,29) , and chicken eggs (3 cats) 12,17) . In our study, a few cats were determined to be sensitive to milk, fish, or beef.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Numerous dietary items have been reported to cause CFA in cats ( Table 1). The most commonly identified items were cow's milk (15 cats) 4,12,17,29,31) , fish (10 cats) 12,17,23,31) , beef (10 cats) 12,17,29) , chicken (4 cats), 17,22,29) , and chicken eggs (3 cats) 12,17) . In our study, a few cats were determined to be sensitive to milk, fish, or beef.…”
Section: Discussionmentioning
confidence: 99%
“…Wherein single dietary items were sequentially used in provocative exposure trials 20) , most cats were found to be sensitive to only 1 ingredient. Two cats were determined to be sensitive to 5 dietary items each 17) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations